Resource Competition Affects Plankton Community Structure; Evidence from Trait-Based Modeling - Sourisseau, Marc; Le Guennec, Valerie; Le Gland, Guillaume; Plus, Martin; Chapelle, Annie (Frontiers in Marine Science, 2017)
Understanding the phenology of phytoplankton species is a challenge and despite a lot of theoretical work on competition for resources, this process is under-represented in deterministic models. To study the main driver of the species selection, we used a trait-based model that keeps phenotypic variability through physiological trait parameterization. Next, we validated the results by using the toxic dinoflagellate Alexandrium minutum which is a toxic species. Due to their monitoring, we show that harmful algae are ideal models for studying ecological niches and for contributing to this more global challenge. As a first step, a dimensionless model of an estuary (France) was built with water temperature and water exchanges deduced from a hydro-dynamic model. The biological parametrization takes into account the size (from pico- to microphytoplankton) and the type of assimilation. The results show that temperature, competition for nutrients and dilution are important factors regulating the community structure and Alexandrium minutum dynamics (more especially the bloom initiation and magnitude). These drivers contribute to the determination of the ecological niche of A. minutum, influence the shape of its blooms and provide potential explanations of its interannual variability. This approach makes the community structure more flexible in order to study how environmental forcings could drive its evolution.